Simultaneous specification of amplitudes and directions of bimanual reversal movements - Heuer, H. (Journal of Motor Behavior, 2006)
Intermanual interactions are modulated by task requirements in the course of motor preparation. In particular, amplitude coupling is strong when identical amplitudes are specified concurrently for the 2 hands but relaxed when different amplitudes are specified. Similarly, directional coupling is symmetric when symmetric directions are specified concurrently but turns to parallel when parallel directions are specified. Here, the author investigated whether the modulations of amplitude coupling and directional coupling in the course of motor preparation are independent or interact. Application of the timed-response procedure, which enables one to manipulate the time available for motor preparation, in 9 participants revealed a weakly interactive pattern. Directional coupling tended to be reduced when different rather than same amplitudes were specified concurrently, and amplitude coupling tended to be reduced when parallel rather than symmetric directions were specified concurrently. In general, interactive effects were also apparent in the rates at which directions and amplitudes were specified. Those observations are consistent with the notion that intermanual amplitude and direction interference are mediated by different but partially overlapping neural structures.